Chiral Transition Metal Oxides: Synthesis, Chiral Origins, and Perspectives. Issue 41 (2nd August 2020) - Li, Yiwen; Wang, Xiongbin; Miao, Jun; Li, Jiagen; Zhu, Xi; Chen, Rui; Tang, Zikang; Pan, Ruikun; He, Tingchao; Cheng, Jiaji
Abstract: Transition metal oxides (TMOs) consist of a series of solid materials, exhibiting a wide variety of structures with tunability and versatile physicochemical properties. Such a statement is undeniably true for chiral TMOs since the introduction of chirality brings in not only active optical activities but also geometrical anisotropy due to the symmetry‐breaking effect. Although progressive investigations have been made for accurately controlled synthesis and relevant explanations on the chirality origin of such materials, the overall field of chiral TMOs is still in its infancy with adequate space for interdisciplinary communications and development. Herein, therefore, recent advances in both experimental phenomena and theoretical calculations in this area are reviewed, to elucidate the underlying chiral origin with respect to their fabrications process, triggering new insights for further evolution of this field. Abstract : Transition metal oxides with induced chirality have revolutionized the area of chiroptics and motifs of fundamental research on chiral origin of inorganic nanomaterials with chiral morphologies or chiral interactions with the environment, demonstrating capacities of such unique classes of nano‐ to microscale materials for the applications in environmental remediation, stereoselective synthesis, and biological science.